A multi-sectorial approach for addressing the problem of snakebite envenoming in Honduras. (1st March 2019) - Alger, Jackeline; Boza-Oviedo, Eduardo Enrique; Mejía, Rosa Elena; Navas, Fanny; Simons-Morales, Perla; Velázquez, Reina Teresa; Gutiérrez, José María
Graphical abstract: Image 1